JAYA ANGGADA - Anak Agung Gede Angga Mahputra; I Ketut Sariada; I Gede Oka Surya Negara (Jurnal IGEL : Journal Of Dance, 2022)
JAYA ANGGADA Creative sources of Jaya Anggada dance works inspired by Anggada, a very agile and nimble character, one of the ape troops of the Ramayana story. During the Great War of Alengka, Anggada shows his heroism on the battlefield, Anggada had to fight Indrajit face-to-face, Indrajit is the crown prince of Alengka, the son of Dewi Tari, who is also his own cousin. Upon his victory, for his service, Anggada awarded “Jaya” which means victorious. Therefore, he is commonly known as Jaya Anggada. The Jaya Anggada dance is created through a process of creation using the Alma. M. Hawkins’ creation method which consists of exploration, improvisation, and forming stages. The cultivation of the Jaya Anggada dance is manifested in the form of structures, namely pengawit, batel, papeson, pengawak, and pengecet. The message to be conveyed from Jaya Anggada dance works is to reshape some unique and quality movements. Key Words : Anggada, Jaya Anggada, Creation